Modifikasi Blender Dapur Menjadi Blender Santan Rumahan - Zakir Husin; Herdi Susanto; Masykur Masykur; Nasri Agus Saputra (universitas teuku umar, 2020)
Nowadays, there are many tools for processing coconut milk, such as grater machines, hydraulic coconut squeezing machines and others, but they are large in size and less efficient for daily use. The purpose of this research is to redesign an ordinary blender to become a coconut milk production blender and to manufacture an ordinary blender to become a coconut milk production blender and to do the testing. The designs that are carried out are the components of the blender mechanism, the grate, and the inner tube. Modifying an ordinary blender into a coconut milk blender by adding an inner tube and drawing it with AutoCAD 2007. After testing the grated and squeezed coconut blender it went well with the grated yield obtained of 1.15 kg from 5 coconuts and the yield of coconut milk obtained during the test was 1.66 liters from 5 coconuts.